Temperature-enhanced synthesis of DMSO-Melanin - Piacenti-Silva, Marina [UNESP]; Bronze-Uhle, Erika Soares [UNESP]; Paulin, João Vitor [UNESP]; Graeff, Carlos Frederico de Oliveira [UNESP] (Elsevier B.V., 2014)
Melanins are a class of pigmentary conjugated macromolecules found in many biological systems. Functionalization of synthetic melanin provides interesting new properties like the greater solubility of melanin synthesized in dimethyl sulfoxide, D-Melanin. In this work we have studied the influence of temperature on D-Melanin synthesis and its properties. To this end, UV-Vis, Fourier-transform infrared (FTIR) spectroscopy and Nuclear Magnetic Resonance (NMR) techniques have been employed to analyze D-Melanin synthesized within the range of 25-100 degrees C. Our results reveal that by increasing the synthesis temperature up to 100 degrees C, the synthesis time can be decreased by a factor of 7 when compared to room temperature. From FTIR and C-13 CP/MAS NMR analyses the increase in temperature causes a decrease in the number of carbonyl groups from carboxylic acid and from ionized carboxylic acid. The decarboxylation of D-Melanin monomers at higher temperatures shows that the use of higher synthesis temperatures influences the elimination of carbonyls present in the precursor molecules, thus facilitating the polymerization of D-Melanin. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Melanin; Dimethyl sulfoxide; Synthesis; Temperature; Optimization; Photoabsorption